Aggregation-induced emission metal organic framework, preparation method thereof and fluorescence / colorimetric dual-mode intelligent detection for trace HCl

By developing ZIF-90-HDBB, aggregating the luminescent metal organic framework material, and loading it on a paper-based sensor, combined with the smartphone color recognition APP, efficient and portable hydrogen chloride gas detection is achieved, solving the problems of difficulty in detection and complex equipment in the prior art.

CN119661862AActive Publication Date: 2025-03-21LIAONING UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411805923.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-21
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The prior art is difficult to achieve efficient, fast and portable hydrogen chloride (HCl) gas detection, and traditional methods require expensive large-scale instruments and professional operations.

Method used

A metal organic framework material ZIF-90-HDBB based on aggregation-induced luminescence was developed. The material was prepared by solvothermal method and evenly loaded on cellulose filter paper to prepare a paper-based sensor, and combined with a smartphone color recognition APP, the rapid detection of fluorescence/colorimetric dual modes was achieved.

Benefits of technology

It realizes sensitive detection of HCl gas, with a detection range of 0-100ppm, a detection limit as low as 3.0ppm, and the material has good stability and recycling performance, which is suitable for rapid on-site inspection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661862A_ABST
    Figure CN119661862A_ABST
Patent Text Reader

Abstract

The invention discloses an aggregation-induced emission metal organic framework, a preparation method thereof and application to fluorescence / colorimetric dual-mode intelligent detection of trace HCl. According to the aggregation-induced emission metal organic framework, Zn < 2 + > provided by Zn (NO3) 3.6 H2O, imidazole-2-formaldehyde and AIE molecule HDBB serve as organic ligands, ZIF-90-HDBB is obtained through a solvothermal method, and after the material is in contact with HCl gas, aggregation-state fluorescence of the material can be changed into orange red from yellow green; zIF-90-HDBB is uniformly loaded on cellulose filter paper to obtain the portable paper-based sensor for detecting HCl, and the portable paper-based sensor is combined with a smart phone color recognition APP to realize rapid and sensitive HCl fluorescence / colorimetric dual-mode field detection. As HDBB molecules are easy to generate protonation under an acidic condition to generate fluorescence color conversion, the material can be accurately and efficiently used for detecting acidic gas, and the material can be recycled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fluorescent sensing materials, and the technology relates to aggregation-induced luminescent metal organic coordination polymers, and specifically to aggregation-induced luminescent metal organic frameworks and preparation methods thereof, and fluorescent / colorimetric dual-mode intelligent detection for trace HCl. Background Art

[0002] Excessive concentration of toxic chemical gases can cause great damage to the environment and human health, so the efficient detection of toxic gases has attracted increasing attention. One of the important and harmful gases, hydrogen chloride (HCl) gas, is produced in large quantities in fertilizer production, electroplating, textile and rubber industries. When the human body is suddenly exposed to this gas, it can cause hoarseness, respiratory ulcers and pulmonary edema. In addition, as a highly toxic and corrosive substance, the workplace exposure limit of HCl gas is 5ppm. The human body's exposure limit is 50-100ppm of HCl vapor, and when the human body is exposed to 1300-2000ppm of HCl vapor, it will be fatal. Therefore, it is of practical significance to be able to detect toxic gas HCl in a real environment. Traditional HCl gas detection methods mainly include gas chromatography, chromatography-mass spectrometry, electrochemical detection, etc., but these methods require expensive and sophisticated large-scale instruments, and also require specialized technical operators, making it difficult to achieve efficient and rapid on-site detection. Efficient and intuitive HCl gas detection methods have become a more concerned issue.

[0003] Photochemical sensing methods have attracted extensive attention from researchers due to their high sensitivity, fast response speed, simple instrumentation, and visualization. Among photochemical sensing materials, the luminescent properties of luminescent metal organic framework materials are mainly due to the fluorescent properties of organic ligands and the specificity of metal ions or metal clusters. Therefore, a novel fluorescent material can be obtained by rationally adjusting the ligands of MOFs materials. Summary of the invention

[0004] The purpose of the present invention is to provide a metal organic framework material based on aggregation induced luminescence, a preparation method and its application. The preparation method has low equipment requirements and is simple to operate; the prepared materials HDBB and ZIF-90-HDBB have good aggregation induced luminescence performance and can sensitively detect hydrogen chloride gas.

[0005] An aggregation-induced emission metal-organic framework, Zn(NO3)3.6H2O provides Zn 2+ , imidazole-2-carboxaldehyde and AIE molecule HDBB as organic ligands, and the aggregation-induced emission metal-organic framework material ZIF-90-HDBB was obtained by a solvothermal method.

[0006] The above-mentioned method for preparing an aggregation-induced emission metal-organic framework comprises dissolving imidazole-2-carboxaldehyde ICA and polyvinylpyrrolidone PVP in deionized water, heating the solution in a water bath to obtain solution 1, dissolving HDBB in a Tris-HCl solution, and ultrasonically obtaining solution 2. After solution 1 is cooled to room temperature, solution 2 is added to solution 1, and the solution is slightly shaken. A Zn(NO3)2.6H2O solution is dripped into the above-mentioned mixed solution drop by drop, and the mixed solution is allowed to stand. After centrifugation and washing, an aggregation-induced emission metal-organic framework material ZIF-90-HDBB can be obtained.

[0007] In the above-mentioned method for preparing an aggregation-induced emission metal organic framework, the water bath heating is water bath heating at 80° C. for 0-20 min.

[0008] In the above-mentioned method for preparing an aggregation-induced emission metal organic framework, the molar ratio of Zn(NO3)2.6H2O to ICA is 1:4.

[0009] The above-mentioned method for preparing an aggregation-induced emission metal organic framework, the method for preparing HDBB, specifically comprises the following steps:

[0010] Dissolve 4-formyl-3-hydroxybenzoic acid in methanol, add hydrazine hydrate after dissolution, reflux in an oil bath at 75°C for 12 hours, cool to room temperature after the reaction, wash with methanol, and vacuum dry to obtain a yellow HDBB solid product.

[0011] A probe dispersion liquid is prepared by dissolving the above ZIF-90-HDBB in a methanol / DMSO solution and uniformly dispersing the solution by ultrasonication to obtain a probe dispersion liquid with a concentration of 1 mg / mL.

[0012] The preparation of the above-mentioned aggregation-induced emission metal organic framework and its application in fluorescence detection of trace HCl solution are as follows:

[0013] 1) Add the above 1 mg / mL probe dispersion to a solution containing 0-0.4 μM HCl and perform fluorescence testing to obtain a linear relationship between HCl concentration and fluorescence intensity, y=2.9933C-0.2799, R 2 =0.9958,

[0014] 2) Add the above 1 mg / mL probe dispersion to the HCl solution to be tested and perform fluorescence test. According to the fluorescence intensity,

[0015] Substitute into the linear equation obtained in step 1) to calculate the concentration of the HCl solution.

[0016] The preparation of the above-mentioned aggregation-induced emission metal organic framework and its use in fluorescence detection of trace HCl gas are as follows:

[0017] 1) In a sealed container, the above-mentioned 1 mg / mL probe dispersion was placed, and the injected HCl solution was heated and volatilized to generate 0-50 ppm HCl gas in the device. After 10 minutes, the probe solution was taken out and fluorescence test was performed to obtain the linear relationship between HCl gas concentration and fluorescence intensity, y=0.01536c+0.02353, R 2 =0.9921;

[0018] 2) In a sealed container, put the above-mentioned 1 mg / mL probe dispersion, place the HCl gas to be tested in a sealed device, take out the probe solution after 10 minutes, perform fluorescence test, and calculate the concentration of HCl gas based on the fluorescence intensity, the linear equation obtained in step 1) and pV=nRT.

[0019] A paper-based sensor is prepared by dissolving the above-mentioned ZIF-90-HDBB in a nitrogen methyl pyrrolidone solution to obtain a probe dispersion liquid with a concentration of 1 mg / mL, soaking cellulose filter paper in the probe dispersion liquid for 12 hours, and drying the paper-based sensor.

[0020] The above-mentioned aggregation-induced emission metal organic framework is prepared and used for colorimetric dual-mode intelligent detection of trace HCl gas, and the method is as follows:

[0021] 1) Place the above-mentioned paper-based sensor in a sealed container, inject HCl solution and volatilize it by heating to generate 0-100ppm HCl gas in the device. After 10 minutes, take out the paper-based sensor and obtain its R / G value through color recognition APP under 360nm ultraviolet light. The linear equation of R / G value and HCl gas is obtained, y=0.07248c+0.8865, R 2 =0.9650;

[0022] 2) Place the above-mentioned paper-based sensor in a sealed container, place the HCl gas to be measured in a sealed device, take it out after 10 minutes, and obtain its R / G value through color recognition APP under a 360nm ultraviolet lamp. Calculate the concentration of HCl gas according to the linear equation of step 1).

[0023] The concentration range of the aggregation-induced luminescence metal organic framework material to HCl is 0.1-0.4 μM (detecting HCl solution) and 0-100 ppm (detecting HCl gas).

[0024] The aggregation-induced emission metal organic framework material ZIF-90-HDBB of the present invention has the advantages of good stability, high fluorescence intensity, etc. Due to the introduction of the ligand AIE molecule HDBB, the material has potential application in acid gas detection.

[0025] The present invention uniformly loads the material ZIF-90-HDBB on cellulose filter paper to prepare a portable paper-based sensor for detecting HCl gas. By combining with a smartphone color recognition APP, rapid and sensitive on-site detection of HCl gas in fluorescence / colorimetry dual modes can be achieved. The present invention utilizes the aggregation-induced luminescence performance of aggregation-induced luminescence molecules to obtain an aggregation-induced luminescence metal-organic framework material. Since HDBB molecules are easily protonated under acidic conditions to produce a change in fluorescence color, they can be accurately and efficiently used for the detection of acidic gases, and the material can also be repeatedly recycled. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the aggregation-induced emission metal-organic framework ZIF-90-HDBB for detecting HCl.

[0027] Figure 2 Schematic diagram of the synthesis of AIE molecule HDBB.

[0028] Figure 3 This is the H NMR spectrum of the AIE molecule HDBB ( 1 H-NMR) and carbon nuclear magnetic resonance spectra ( 1 C-NMR).

[0029] Figure 4 Schematic diagram of the synthesis of aggregation-induced emission metal-organic framework ZIF-90-HDBB.

[0030] Figure 5 FT-IR spectra (a) and XRD spectra (b) of AIE molecule HDBB, metal organic framework ZIF-90 and aggregation-induced emission metal organic framework ZIF-90-HDBB.

[0031] Figure 6 XPS spectra of the synthesized metal-organic framework ZIF-90 and aggregation-induced emission metal-organic framework ZIF-90-HDBB.

[0032] Figure 7 Solid-state fluorescence spectra of AIE molecule HDBB and aggregation-induced emission metal-organic framework ZIF-90-HDBB.

[0033] Figure 8 Fluorescence emission spectra of different ligand ratios for the synthesis of aggregation-induced emission metal-organic framework ZIF-90-HDBB.

[0034] Fig. 9 SEM images of different ligand ratios for the synthesis of aggregation-induced emission metal-organic framework ZIF-90-HDBB.

[0035] Fig.10TEM image of the optimal ligand ratio for the synthesis of aggregation-induced emission metal-organic framework ZIF-90-HDBB.

[0036] Fig.11 Thermogravimetric curve of the material with the optimal ligand ratio for synthesizing aggregation-induced emission metal-organic framework ZIF-90-HDBB.

[0037] Fig.12 To characterize the aggregation-induced emission properties of the aggregation-induced emission metal-organic framework ZIF-90-HDBB, (a) and (c) are the fluorescence spectra of HDBB and ZIF-90-HDBB in different aggregation states; (b) and (d) are the change curves of the fluorescence intensity of HDBB and ZIF-90-HDBB in different aggregation states.

[0038] Fig.13 This is the N2 adsorption diagram of the aggregation-induced emission metal-organic framework ZIF-90-HDBB.

[0039] Fig.14 The UV-visible absorption spectra (a) and optimal excitation / emission spectra (b) of the AIE molecule HDBB, metal organic framework ZIF-90 and aggregation-induced emission metal organic framework ZIF-90-HDBB. The inset in (a) is the optical image of ZIF-90-HDBB under fluorescent light (left) and 365nm UV light (right).

[0040] Fig.15 The response of ZIF-90-HDBB after detecting different acidic gases (a) and the changes in emission wavelength and intensity of ZIF-90-HDBB after detecting different acidic gases (b).

[0041] Fig.16 This is a linear relationship diagram between the fluorescence emission spectrum of the aggregation-induced emission metal organic framework ZIF-90-HDBB in 0-0.4 μM HCl solution and the HCl concentration.

[0042] Fig.17 This is a linear relationship diagram between the fluorescence emission spectrum of the aggregation-induced emission metal organic framework ZIF-90-HDBB after detecting 0-50ppm HCl gas and the HCl gas concentration.

[0043] Fig.18 XRD spectrum of aggregation-induced emission metal-organic framework ZIF-90-HDBB after detecting 0-1000ppm HCl gas.

[0044] Fig.19 The response time and cycling performance of the aggregation-induced emission metal-organic framework ZIF-90-HDBB for HCl gas detection.

[0045] Fig. 20 Actual photos and scanning electron microscope images of the paper-based sensor prepared by loading the aggregation-induced emission metal-organic framework ZIF-90-HDBB on cellulose filter paper.

[0046] Fig.21 The linear relationship between the actual photo of the paper-based sensor detecting 0-100ppm HCl gas and the HCl gas concentration.

[0047] Fig. 22 A paper-based sensor combined with a smartphone color recognition APP to detect HCl gas. DETAILED DESCRIPTION

[0048] Example 1 Aggregation-induced emission molecule HDBB

[0049] (a) If Figure 2 As shown, the preparation method is as follows:

[0050] 166.2 mg of 4-formyl-3-hydroxybenzoic acid was dissolved in 10 mL of methanol. After complete dissolution, 24 μL of hydrazine hydrate was added thereto and refluxed at 75° C. for 12 h. After the reaction was completed, the product was washed with methanol to obtain a yellow HDBB product.

[0051] (II) Characterization of HDBB

[0052] For the H NMR spectrum test of HDBB, take about 10 mg of vacuum-dried HDBB and dissolve it in deuterated DMSO. After it is completely dissolved, the test can be performed. For the C NMR spectrum test of HDBB, take about 100 mg of HDBB and dissolve it in deuterated DMSO. After it is completely dissolved, the test can be performed. The test results are as follows: Figure 3 As shown in (a), the two single peaks with chemical shift δ located at 13.25 and 11.15 are typical characteristic peaks of hydrogen on the carboxyl group and hydrogen on the hydroxyl group, the single peak at 9.04 is the characteristic peak of hydrogen in the carbon-hydrogen bond connected to the nitrogen atom, and the hydrogen on the benzene ring δ is located in the range of 7.88-7.50. Figure 3 As shown in (b), the test results of the carbon NMR spectrum corroborated the test results of the hydrogen NMR spectrum, confirming the successful synthesis of HDBB.

[0053] Example 2 Aggregation-induced emission metal organic framework ZIF-90-HDBB

[0054] (a) If Figure 4 As shown, the preparation method is as follows:

[0055] Dissolve 5.00mmol of imidazole-2-carboxaldehyde (ICA) and 0.43mmol of polyvinylpyrrolidone (PVP) in 25mL of deionized water, heat in a water bath at 80℃ for 10min to obtain solution 1, dissolve 0-0.1mmol of HDBB in 40μLTris-HCl solution, ultrasonicate for 10min to obtain solution 2, after solution 1 is cooled to room temperature, add solution 2 to solution 1, and shake gently for 20min. Add 5mL of Zn(NO3)2.6H2O solution dropwise into the above mixed solution, the molar ratio of Zn(NO3)2.6H2O to ICA is 1:4, and stand for 24h. After centrifugation and washing with deionized water, the aggregation-induced emission metal organic framework material ZIF-90-HDBB can be obtained.

[0056] Screening of the optimal ratio of test solvents for HDBB and ZIF-90-HDBB: To verify the effect of solvent properties on the aggregation-induced luminescence properties of HDBB and ZIF-90-HDBB, 10 mg of HDBB molecules prepared in Example 1 and 5 mg of ZIF-90-HDBB molecules prepared in Example 2 were taken and dissolved in 5 mL of methanol to obtain solutions with concentrations of 2 mg / mL and 1 mg / mL, respectively. 0.5 mL of the above solutions were taken respectively, and a mixed solution of methanol and DMSO with different volume proportions was added thereto to ensure that the final test solution volume was 5 mL, and HDBB (0.2 mg / mL) and ZIF-90-HDBB (0.1 mg / mL) test solutions with different methanol proportions were obtained.

[0057] (II) Characterization of ZIF-90-HDBB

[0058] Figure 5 FT-IR images of HDBB, ZIF-90 and ZIF-90-HDBB (a) and XRD spectra of ZIF-90 and ZIF-90-HDBB (b). Figure 5 As can be seen from (a), the main characteristic peak of HDBB is 1623 cm -1 The C=O vibration peak at 3346 cm -1 The OH vibration peak at 1600 cm -1 、1564cm -1 The characteristic peak of benzene ring is at 2850cm -1 CH stretching vibration and 1675 cm -1 Comparing the FT-IR spectra of ZIF-90 and ZIF-90-HDBB, it can be seen that the peak at 1675 cm-1 appears in ZIF-90-HDBB. -1The C=O stretching vibration peak at shows that ZIF-90-HDBB has a similar functional group structure to ZIF-90, but the C=O vibration peak and OH vibration peak of HDBB are bound to zinc ions and are shielded by ZIF-90, so the characteristic peaks of HDBB do not appear in ZIF-90-HDBB. This shows that the AIE molecule HDBB is encapsulated in the skeleton structure of ZIF-90 rather than simply adsorbed on its surface. Figure 5 From the X-ray diffraction comparison of ZIF-90 and ZIF-90-HDBB in (b), it can be seen that each diffraction peak of ZIF-90-HDBB corresponds one-to-one with that of ZIF-90, confirming that ZIF-90-HDBB retains the crystal structure of ZIF-90 and proving the successful synthesis of ZIF-90-HDBB.

[0059] Figure 6 The X-ray photoelectron spectra (XPS) of ZIF-90 and ZIF-90-HDBB are shown in Figure 2. The chemical composition of ZIF-90-HDBB was further analyzed by XPS. Figure 6 shown. Figure 6 (a) is the high-resolution Zn2p XPS spectra of ZIF-90 and ZIF-90-HDBB. Compared with ZIF-90, the characteristic peak of ZIF-90-HDBB has shifted, indicating that the coordination environment of Zn has changed. This is mainly due to the introduction of a new ligand HDBB in ZIF-90, forming a new skeleton ZIF-90-HDBB. The high-resolution C1s XPS spectrum of ZIF-90-HDBB has three peaks at 288.43ev, 285.99ev, and 284.58ev, which are C≡N, CN, and CC / C=O, respectively. Compared with ZIF-90, the C1s peak in ZIF-90-HDBB has different degrees of shift, indicating that the chemical environment of the C atom in ZIF-90-HDBB has changed, further proving the synthesis of ZIF-90-HDBB.

[0060] Figure 7 The solid fluorescence spectra of HDBB and ZIF-90-HDBB are shown in Figure 2. Figure 7 It can be seen that both HDBB and ZIF-90-HDBB have certain fluorescence properties. Since HDBB molecules can be used as organic ligands to form metal organic framework materials, they will react with Zn 2+ Through the coordination of metal ions and the three-dimensional structure of the metal organic framework, the rotation of the NN bond of the AIE molecule HDBB is restricted, resulting in the fluorescence intensity of ZIF-90-HDBB being significantly stronger than that of HDBB. This shows that the effective introduction of AIE molecules into the metal organic framework can obtain a more luminescent solid fluorescent material.

[0061] Figure 8 The fluorescence emission spectra of different ligand ratios when synthesizing ZIF-90-HDBB are shown in Figure 2. In order to further improve the fluorescence performance of ZIF-90-HDBB, the synthesis conditions of ZIF-90-HDBB were optimized. The effect of adding different ratios of HDBB and imidazole-2-carboxaldehyde on the fluorescence intensity of ZIF-90-HDBB was investigated. It can be seen from the fluorescence spectrum that when the ratio of HDBB to 2-methylimidazole is 2.1:1 and 4.1:1, the fluorescence emission is weak. When the ratio of HDBB to 2-methylimidazole is 16.4.:1, the fluorescence intensity of the material is close to the maximum value. The content of HDBB molecules is continued to increase. When the ratio of HDBB to 2-methylimidazole reaches 32.8:1, the increase in fluorescence intensity is very small.

[0062] Fig. 9 The following are SEM images of different ligand ratios for synthesizing ZIF-90-HDBB. From 9(a), it can be seen that the morphology of ZIF-90 is a regular dodecahedron with an average diameter of about 2-5μm. After adding HDBB molecules, as the amount of HDBB added increases, the morphology of ZIF-90-HDBB is gradually destroyed, and the growth of the material morphology gradually tends to be irregular. Combined with the fluorescence emission spectra of different ligand ratios of the material, the ratio of HDBB to imidazole-2-carboxaldehyde is 16.4:1 as the optimal addition amount. The subsequent performance and characterization tests of the material also select ZIF-90-HDBB synthesized under this ligand ratio.

[0063] Fig.10 TEM images of ZIF-90 and aggregation-induced emission metal-organic framework ZIF-90-HDBB. Fig.10 (a) is the TEM image of ZIF-90. Fig.10 (b) is the TEM image of ZIF-90-HDBB. It can be seen from the figure that ZIF-90-HDBB appears as a dodecahedron with disrupted growth, and its average diameter is close to that of ZIF-90.

[0064] Fig.11 Thermogravimetric curves of HDBB, ZIF-90, and ZIF-90-HDBB. Fig.11 (c) It can be seen that ZIF-90 does not lose weight before 300°C, and the organic ligand molecules lose weight between 350-400°C. When the temperature rises to 400°C, the ZIF-90 skeleton collapses. Fig.11(b) It can be seen that the HDBB molecule loses weight due to water molecules before 100°C. For the ZIF-90-HDBB molecule, its weight loss before 100°C is caused by water molecules, and its weight loss between 100-350°C and part of its weight loss between 420-800°C are caused by doped HDBB molecules. The effective doping amount of HDBB molecules is calculated to be about 20.07%.

[0065] Fig.12 To characterize the aggregation-induced luminescence performance of the aggregation-induced luminescence metal organic framework ZIF-90-HDBB, (a) and (c) are the fluorescence spectra of HDBB and ZIF-90-HDBB in different aggregation states; (b) and (d) are the curves of the change of fluorescence intensity of HDBB and ZIF-90-HDBB in different aggregation states. DMSO is a good solvent for HDBB and ZIF-90-HDBB, and methanol is a poor solvent for HDBB and ZIF-90-HDBB. It can be seen from the figure that with the increase of methanol content, the fluorescence intensity of HDBB and ZIF-90-HDBB also gradually increases. This is mainly because in poor solvents, the material is more inclined to form aggregates, which restricts the molecular motion and releases energy in the form of fluorescence. When methanol / DMSO is 9:1, the material has the maximum fluorescence intensity; for ZIF-90-HDBB molecules, when methanol / DMSO is 7:1, the material has the maximum fluorescence intensity.

[0066] Fig.13 The N2 adsorption-desorption isotherms of ZIF-90 and ZIF-90-HDBB are shown in Figure 2. The specific surface area and pore structure of the material are crucial to the sensing performance of the material, so the N2 adsorption-desorption isotherms of ZIF-90 and ZIF-90-HDBB were measured. Fig.13 As shown in the figure, the adsorption isotherms of ZIF-90 and ZIF-90-HDBB are obvious type IV isotherms, and there are abundant mesoporous structures in the materials. However, there are slight differences in the hysteresis types of ZIF-90 and ZIF-90-HDBB. Compared with ZIF-90, ZIF-90-HDBB shows a slight saturated adsorption platform when (P / P0)≥0.6. These results indicate that there is randomness in the pore structure of ZIF-90-HDBB, which is attributed to the introduction of HDBB molecules into the metal organic framework material. The BET specific surface areas of ZIF-90 and ZIF-90-HDBB are 175.41 m 2 / g and 220.54m 2 / g, and the pore volume is 0.28cm 3 / g and 0.34cm 3 / g. The changes in surface area and pore volume after modification are consistent with previous reports, which is mainly due to the longer molecular chain of the introduced HDBB. For metal organic framework materials, long ligand molecules will lead to a larger pore structure in the material, resulting in a larger specific surface area.

[0067] Fig.14 The UV-visible absorption spectra (a) and optimal excitation / emission spectra (b) of HDBB, ZIF-90, and ZIF-90-HDBB. The inset in (a) is an optical image of ZIF-90-HDBB under fluorescent light (left) and 365nm UV light (right). Fig.14 (a) It can be seen that HDBB has n-π at 320nm and 400nm * and π-π * The ZIF-90-HDBB exhibits an absorption peak at 280 nm belonging to ZIF-90, and the absorption peak at 400 nm is the π-π transition absorption of the HDBB molecule. * Transition absorption peak. ZIF-90-HDBB shows yellow-green emission in the aggregated state. Fig.14 It can be seen from (b) that the fluorescence emission intensity of ZIF-90-HDBB is much higher than that of HDBB molecules, which is mainly due to the fixation of organic ligand molecules HDBB in the framework of ZIF-90-HDBB, indicating that HDBB molecules coordinate with metal ions to form ZIF-90-HDBB, which can effectively inhibit the rotation of the NN bond in HDBB. The optimal excitation wavelength and emission wavelength of ZIF-90-HDBB are 446nm and 532nm respectively.

[0068] Fig.15 The response of ZIF-90-HDBB after detecting different acidic gases (a) and the change of emission wavelength and intensity after ZIF-90-HDBB detects different acidic gases (b). It can be seen from the figure that after the material ZIF-90-HDBB detects 100ppm HCl gas, the fluorescence intensity of the material will drop significantly, and the emission wavelength will move toward the long wavelength direction. ZIF-90-HDBB shows negligible fluorescence intensity changes for 100ppm other acidic volatile gases, indicating that it has good selectivity for HCl gas.

[0069] Example 3 Recognition of HCl by the aggregation-induced emission metal organic framework ZIF-90-HDBB

[0070] Test solution preparation: 20 mg of ZIF-90-HDBB prepared in Example 2 was dissolved in 20 mL of a 9:1 methanol / DMSO solution, and ultrasonically dispersed to obtain a probe dispersion with a concentration of 1 mg / mL.

[0071] Detection of HCl solution: Prepare 0.01 mol / L HCl stock solution, then dilute it to 0.1-0.4 μM, add 50 μL of the diluted HCl solution of different concentrations to 5 mL, 1 mg / mL probe solution, and then perform fluorescence test.

[0072] HCl gas detection: HCl gas detection is carried out in a homemade 18L sealed container. The HCl solution is injected into the container through the small hole with a rubber plug on the top of the device with a syringe. The heating device in the container will evaporate the HCl solution into gaseous HCl. 1mg / mL, 5mL of probe dispersion is placed in the above sealed container and taken out after 10 minutes for fluorescence testing. The concentration of HCl gas can be calculated by the ideal gas state equation pV=nRT.

[0073] Fig.16 The fluorescence emission spectrum of the probe response after adding 0-0.4 μM HCl solution (a) and the linear relationship between the probe fluorescence intensity and HCl concentration (b). Fig.16 As shown in (a), as the concentration of HCl increases, the fluorescence intensity of the probe gradually decreases. Fig.16 As shown in (b), the fluorescence intensity of the sensing system has a good linear relationship with the HCl concentration in the range of 0-0.40 μM, R 2 =0.9958, and the detection limit is calculated by the formula D=3σ / K (σ is the standard deviation of the fluorescence intensity of the fluorescent material ZIF-90-HDBB itself, the number of measurements is not less than 20 times, and K is the coefficient of variation of the fluorescence intensity when the fluorescent material ZIF-90-HDBB detects HCl solution). The detection limit of this fluorescent probe for HCl is as low as 0.04μM.

[0074] Fig.17 The fluorescence emission spectrum of ZIF-90-HDBB after detecting 0-50ppm HCl gas (a) and the linear relationship between the probe fluorescence intensity and HCl gas concentration (b). Fig.17 As shown in (a), as the concentration of HCl gas increases, the fluorescence intensity of the probe gradually decreases. Fig.17 As shown in (b), the fluorescence intensity of the sensing system has a good linear relationship with the HCl concentration in the range of 0-50 ppm, R 2 =0.9921, the general formula D=3σ / K (σ is the standard deviation of the fluorescence intensity of the fluorescent material ZIF-90-HDBB itself, the number of measurements is not less than 20 times, K is the fluorescence intensity variation coefficient of the fluorescent material ZIF-90-HDBB when detecting HCl gas) calculates that the detection limit of the fluorescent probe for HCl gas is as low as 3.39ppm.

[0075] Fig.18The changes in the XRD spectrum of ZIF-90-HDBB after testing 0-1000ppm HCl gas. Fig.18 It can be seen that the prepared fluorescent probe ZIF-90-HDBB has good stability, and its structure will only be destroyed when the concentration of HCl gas is as high as 1000ppm, which makes it possible to have further practical applications. Fig.18 To test the cyclic performance and response time of ZIF-90-HDBB for HCl gas detection, the material was heated at 100°C for 30 minutes after detecting 40ppm HCl gas, so that the HCl gas in the pores of the material was separated under heating conditions. After five cycles, the fluorescence intensity of the material only lost 6.5%, proving that the material has good cyclic performance. At the same time, the material can complete the detection of 50ppm HCl gas within 10 minutes, confirming the feasibility of the probe for rapid on-site detection of HCl gas.

[0076] Example 4 Preparation of paper-based sensor

[0077] Preparation of paper-based sensor: Take 20 mg of ZIF-90-HDBB prepared in Example 2 and dissolve it in 20 mL of nitrogen methyl pyrrolidone solution to obtain a probe dispersion with a concentration of 1 mg / mL. Soak a cut circular qualitative filter paper with a diameter of about 1.2 cm in the probe dispersion for 12 hours, take it out and dry it at 30°C for 6 hours to obtain a paper-based sensor.

[0078] Detection of HCl gas: The detection of HCl gas is carried out in a homemade 18L sealed container. The HCl solution is injected into the container through the small hole with a rubber plug on the top of the device with a syringe. The heating device in the container will evaporate the HCl solution into gaseous HCl. The concentration of HCl gas can be calculated by the ideal gas state equation pV=nRT. The prepared paper-based sensor is placed in the above-mentioned sealed container and taken out after 10 minutes. Its R / G value can be obtained by color recognition APP under 360nm ultraviolet light. Fig. 20 The following are the actual photos of the paper-based sensor (a) and its scanning electron microscope image (b). Fig. 20 As can be seen in (a), the prepared paper-based sensor appears yellow under fluorescent light. Fig. 20 As can be seen in (b), the material ZIF-90-HDBB is evenly loaded on the cellulose filter paper.

[0079] Fig.21The actual photo (a) of the paper-based sensor after detecting 0-100ppm HCl gas and the linear relationship between the material and the HCl gas concentration. When the HCl gas concentration increases from 0 to 100ppm, the paper-based sensor shows a continuous color change from yellow-yellow-green-orange-red under 360nm ultraviolet light. Since slight color changes are not easy to observe with the naked eye, we digitally analyze the color information (RGB value) of the fluorescent photo through a color recognition application (Color Grab). After the paper-based sensor detected 0-100ppm HCl gas, a series of photos with colors ranging from yellow-yellow-green-orange-red were taken with a mobile phone camera under 360nm ultraviolet light. The RGB values ​​corresponding to these photos were obtained through the color recognition APP, and further statistical analysis was performed to obtain a linear relationship curve. The results are shown in Fig.21 (b) shows that there is a good linear relationship between the RGB ratio (R / G) and the HCl gas concentration, R 2 =0.9650, and the detection limit is as low as 3.0ppm. The above results prove that the prepared paper-based sensor can realize semi-quantitative, convenient, intuitive, and sensitive intelligent detection of trace HCl gas.

[0080] Fig. 22 The bar graph shows the R / G changes of the paper-based sensor to different acidic gases. In order to prove the selectivity of the material for HCl gas detection, the prepared paper-based sensor responded to 40ppm HCl and other types of acidic gases. The R / G value of the paper-based sensor only changed slightly, which shows that the material has good selectivity for HCl gas.

[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An aggregation-induced emission metal-organic framework, characterized in that: Zn is provided by Zn(NO3)3.6H2O 2+ , imidazole-2-carboxaldehyde and AIE molecule HDBB as organic ligands, and the aggregation-induced emission metal-organic framework material ZIF-90-HDBB was obtained by a solvothermal method.

2. The method for preparing an aggregation-induced emission metal organic framework according to claim 1, characterized in that: Dissolve imidazole-2-carboxaldehyde ICA and polyvinylpyrrolidone PVP in deionized water, heat in a water bath to obtain solution 1, dissolve HDBB in Tris-HCl solution, and obtain solution 2 by ultrasound. After solution 1 is cooled to room temperature, solution 2 is added to solution 1, and the mixture is shaken slightly. Zn(NO3)2.6H2O solution is dripped into the mixed solution drop by drop, and the mixture is allowed to stand. After centrifugation and washing, the aggregation-induced emission metal-organic framework material ZIF-90-HDBB can be obtained.

3. The method for preparing an aggregation-induced emission metal-organic framework according to claim 2, characterized in that: The water bath heating is heating in a water bath at 80° C. for 0-20 min.

4. The method for preparing an aggregation-induced emission metal-organic framework according to claim 2, characterized in that: The molar ratio of Zn(NO3)2.6H2O to ICA is 1:

4.

5. The method for preparing an aggregation-induced emission metal-organic framework according to claim 2, characterized in that: The preparation method of HDBB specifically comprises the following steps: Dissolve 4-formyl-3-hydroxybenzoic acid in methanol, add hydrazine hydrate after dissolution, reflux in an oil bath at 75°C for 12 hours, cool to room temperature after the reaction, wash with methanol, and vacuum dry to obtain a yellow HDBB solid product.

6. A probe dispersion, characterized in that: The ZIF-90-HDBB according to claim 1 is dissolved in a methanol / DMSO solution, and ultrasonically dispersed to obtain a probe dispersion with a concentration of 1 mg / mL.

7. The preparation of an aggregation-induced emission metal organic framework according to claim 1 and its use in fluorescence detection of trace HCl solution, characterized in that: Here is how: 1) Adding the 1 mg / mL probe dispersion of claim 6 to a solution containing 0-0.4 μM HCl, performing fluorescence testing, and obtaining a linear relationship between HCl concentration and fluorescence intensity, y=2.9933C-0.2799, R 2 =0.9958, 2) Adding the 1 mg / mL probe dispersion of claim 6 to the HCl solution to be tested, performing a fluorescence test, and substituting the fluorescence intensity into the linear equation obtained in step 1) to calculate the concentration of the HCl solution.

8. The preparation of an aggregation-induced emission metal organic framework and its use in fluorescence detection of trace HCl gas according to claim 1, characterized in that: Here is how: 1) In a sealed container, the 1 mg / mL probe dispersion of claim 6 is placed, and the injected HCl solution is heated and volatilized to generate 0-50 ppm HCl gas in the device. After 10 minutes, the probe solution is taken out and a fluorescence test is performed to obtain a linear relationship between HCl gas concentration and fluorescence intensity, y=0.01536c+0.02353, R 2 =0.9921; 2) In a sealed container, the 1 mg / mL probe dispersion of claim 6 is placed, and the HCl gas to be tested is placed in a sealed device. After 10 minutes, the probe solution is taken out and a fluorescence test is performed. The concentration of the HCl gas is calculated based on the fluorescence intensity, the linear equation obtained in step 1) and pV=nRT.

9. A paper-based sensor, characterized in that: The ZIF-90-HDBB described in claim 1 is dissolved in a nitrogen methyl pyrrolidone solution to obtain a probe dispersion with a concentration of 1 mg / mL, and a cellulose filter paper is soaked in the probe dispersion for 12 hours and then dried to obtain a paper-based sensor.

10. The preparation of an aggregation-induced emission metal organic framework according to claim 1 and its use in colorimetric dual-mode intelligent detection of trace HCl gas, characterized in that: Here is how: 1) In a sealed container, the paper-based sensor according to claim 9 is placed, and HCl solution is injected to generate 0-100 ppm HCl gas in the device by heating and volatilization. After 10 minutes, the paper-based sensor is taken out, and its R / G value can be obtained by color recognition APP under 360nm ultraviolet light, and the linear equation of R / G value and HCl gas is obtained, y=0.07248c+0.8865, R 2 =0.9650; 2) In a sealed container, the paper-based sensor according to claim 9 is placed, and the HCl gas to be measured is placed in a sealed device and taken out after 10 minutes. Under a 360nm ultraviolet lamp, the R / G value can be obtained by color recognition APP, and the concentration of the HCl gas is calculated according to the linear equation of step 1).

Citation Information

Patent Citations

  • MOF nano sensor, preparation method and application

    CN115791724A

  • Preparation method of nano metal organic complex for cell imaging and copper ion detection

    CN116376038A

  • Preparation method of zeolitic imidazolate framework-90 in water-based system

    US20150191491A1